Life-course socioeconomic status and breast and cervical cancer screening: analysis of the WHO's Study on Global Ageing and Adult Health (SAGE) - Dejana Braithwaite; Tomi Akinyemiju; Kemi Ogunsina; Swati Sakhuja; Valentine Ogbhodo (BMJ Open)
Objectives Socioeconomic differences in screening have been well documented in upper-income countries; however, few studies have examined socioeconomic status (SES) over the life-course in relation to cancer screening in lower-income and middle-income countries. Here, we examine individual, parental and life-course SES differences in breast and cervical cancer screening among women in India, China, Mexico, Russia and South Africa.Setting Data from the WHO's Study on Global Ageing and Adult Health (SAGE) 2007–2008 data were used for survey-weighted multivariable regression analysis. We examined the association between individual, parental and life-course SES in relation to breast and cervical cancer screening using education-based and employment-based measures of SES.Participants 22 283 women aged 18–65 years, recruited from China, India, Mexico, Russia and South Africa.Results Having a college degree (OR 4.18; 95% CI 2.36 to 7.40) increased the odds of breast cancer screening compared with no formal education. Women with higher parental SES were almost 10 times more likely to receive breast cancer screening (OR 9.84; 95% CI 1.75 to 55.5) compared with women with low parental SES. Stable higher life-course (OR 3.07; 95% CI 1.96 to 4.79) increased breast cancer screening by threefold and increased cervical cancer screening by more than fourfold (OR 4.35; 95% CI 2.94 to 6.45); however, declining life-course SES was associated with reduced breast cancer screening (OR 0.26; 95% CI 0.08 to 0.79) compared to low life-course SES.Conclusions Higher individual, parental and life-course SES was positively associated with breast and cervical cancer screening, although education-based SES measures were stronger predictors of screening compared with employment-based measures. Improving knowledge of the benefits of cancer screening and integrating cancer screening into routine healthcare practice for low SES women are actionable strategies that may significantly improve screening rates in low-income and middle-income countries.